Effect of Cauterization on the Subconjunctival Fibrovascular Reaction in Rabbit Eyes. (26th November 2013) - Yalniz-Akkaya, Züleyha; Simsek, Gulcin Guler; Uney, Guner Ozkan; Burcu, Ayse; Ornek, Firdevs
ABSTRACT: Objective: The purpose of our study is to investigate the effect of episcleral cauterization during conjunctival autograft surgery on subconjunctival fibrovascular reaction in rabbit eyes. Methods: Twenty-four healthy male New Zealand white rabbits were divided into Control Group ( n = 12) and Cautery Group ( n = 12). In the Control Group, a 4 × 4 mm free conjunctival graft was elevated, the underlying Tenon's capsule was excised, and the free graft was sutured back to its original place with 10-0 nylon sutures. In the Cautery Group, in addition to the same surgical steps, the episclera was cauterized with six gentle touches before the conjunctival graft was sutured back to its original place. The scleroconjunctival block of the operated area was excised at the first month. The sections were stained with hematoxylin and eosine and Masson trichrome and were evaluated using light microscopy. Results: Subconjunctival collagen fibers were increased, and the fibroblast density increased more significantly in the Cautery Group than in the Control Group. The groups were similar regarding vascularization, lymphocytic, and plasmocytic infiltration. Macrophage density was normal in all animals in both groups. Conclusion: Our histopathological examinations indicate that cauterization seems to lead to an increase in subconjunctival fibrosis at the first postoperative month in rabbit eyes.